Stazione Rogers - Semerani, Luciano (Firenze Architettura, 2017)
Built in 1936, and inaugurated by Benito Mussolini himself on the same day in which the first stone was laid for the “Casa del Fascio”, the “Aquila” refinery became through the years the fulcrum of a series of careful design experiments by Rogers, in representation of BBPR. Thus at the beginning of the 21st century, after a careful restoration by Studio Architetti Semerani e Tamaro, the station devoted to Rogers returns to the city, with the aim of filling in some of the missing sections of the narrative.